2016
DOI: 10.1002/2016gl070994
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling satellite aerosol optical thickness and surface fine particle mass through aerosol liquid water

Abstract: Summertime aerosol optical thickness (AOT) over the southeast U.S. is sharply enhanced over wintertime values. This seasonal pattern is unique and of particular interest because temperatures there have not warmed over the past 100 years. Patterns in surface fine particle mass are inconsistent with satellite reported AOT. In this work, we attempt to reconcile the spatial and temporal distribution of AOT over the U.S. with particle mass measurements at the surface by examining trends in aerosol liquid water (ALW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 88 publications
(142 reference statements)
3
33
0
Order By: Relevance
“…Further, higher correlations are generally found between PM 2.5 and low level AOD (i.e., up to 500 m above the surface; Li et al, ). As noted earlier, aerosol water content, which in this study is simulated differently by MODAL and MOSAIC‐8bins, was found to be a key factor needed to reconcile the apparent disconnect between satellite derived AOD and observed PM 2.5 concentrations (Brock, Wagner, Anderson, Attwood, et al, ; Brock, Wagner, Anderson, Beyersdorf, et al, ; Nguyen, Ghate, et al, ).…”
Section: Analyses Of Wrf‐chem Sensitivity and Fidelitymentioning
confidence: 99%
“…Further, higher correlations are generally found between PM 2.5 and low level AOD (i.e., up to 500 m above the surface; Li et al, ). As noted earlier, aerosol water content, which in this study is simulated differently by MODAL and MOSAIC‐8bins, was found to be a key factor needed to reconcile the apparent disconnect between satellite derived AOD and observed PM 2.5 concentrations (Brock, Wagner, Anderson, Attwood, et al, ; Brock, Wagner, Anderson, Beyersdorf, et al, ; Nguyen, Ghate, et al, ).…”
Section: Analyses Of Wrf‐chem Sensitivity and Fidelitymentioning
confidence: 99%
“…One reason that mean annual temperatures in the southeastern United States decreased in the twentieth century despite overall global-mean warming may be the direct radiative effect of the SOA formed from biogenic volatile organic compounds, known as bSOA [Goldstein et al, 2009;Portmann et al, 2009]. This recent cooling trend may also have contributions from internal variability [Banerjee et al, 2017], aerosol sources aloft [Ford and Heald, 2013], cloud forcing [Yu et al, 2014], particle phase water [Nguyen et al, 2016], and other changes in particle composition [Kim et al, 2015]. The high global flux of biogenic volatile organic compounds of 1000 Tg yr À1 [Guenther et al, 2012] provides ample precursors that may form bSOA in many regions of the world.…”
Section: Introductionmentioning
confidence: 99%
“…Less attention has been given to clear sky and cloudy differences in PM 2.5 chemical composition, especially with regards to particle hygroscopicity and water uptake. Aerosol mass concentrations and chemical speciation including aerosol liquid water (ALW) influence AOT (Christiansen et al, 2019;Malm et al, 1994;Nguyen et al, 2016;Pitchford et al, 2007), cloud microphysics, and mesoscale convective systems (Kawecki and Steiner, 2018), including storm morphology and precipitation patterns (Kawecki et al, 2016). Particle chemical composition modulates particle size via water uptake.…”
mentioning
confidence: 99%